Sinusoidal Three-phase Winding with Maximal Average Span - Bukšnaitis, J. (Elektronika ir Elektrotechnika, 2005)
Three-phases two-layer windings were explored in this article. The sinusoidal three-phase winding with maximal average span can be made on the background of them. It was established that such winding can be made from simple two-layers concentric three-phase winding. It satisfies structural requirements for sinusoidal three-phase winding of the electrical diagram. For each phase of this group of the pulsating periods of magnetomotive force conditioned by the main group of the coils, with respect to the axes formed by the two same groups, are whole symmetrical with respect to the axes of the considered groups.The steps of these main coils groups are equal to the poles step. There was presented analytical expressions of measurement of the number of coils turns of sinusoidal three-phase winding by optimating pulsating and rotating magnetomotive forces. Also there was presented analytical expressions of calculated windings factor. It was shown that winding factor of sinusoidal three-phase winding can be calculated for separate section adding all winding factors. It was explored two-poles sinusoidal winding. They were compared according to appropriate rates. Ill. 1, bibl. 9 (in Lithuanian; summaries in Lithuanian, English and Russian).